The Pasig confluence a multi-modal transportation, commercial, and cultural hub along the banks of the Pasig Rivers and Marikina River - Fernandez, Gabrielle A.; Meonada, Jose Mari (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
As the level of urbanization exponentially increases on national and regional levels, so does the need and demand for mobility and development in transport infrastructure. The constant worsening state of traffic, along with underinvestment and lack of proper maintenance of public transport facilities has produced a cost of three and a half billion pesos in lost opportunities per day, thus requiring the public and private sectors to invest and develop alternative means of transport, especially along waterways such as the Pasig River. This study integrated the plans and programs of the Pasig River Rehabilitation Commission and the Pasig River Ferry Convergence Program into an architectural program for a transport-oriented mixed-use development along the Pasig River. The final product is a comprehensive design project that includes a multi-modal transportation hub - incorporating the projected expansions of the existing Pasig River Ferry Service as well as operational public utility vehicle routes in the district - along with a commercial center that houses dining, retail, and service establishments. The proposed architectural design also includes community spaces for congregation and recreational activity, built around a riverfront park and esplanade.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Multi-modal transportation hub -- Design